Psychotherapy and counselling as a tool for promoting dignity in mental health - Ben Wright; Gabriel Ivbijaro; Isatou N’Jie (Academia Mental Health & Well-Being)
Global advances in access to psychological therapies have created opportunities to understand how counselling and psychotherapy promote dignity, recovery, and well-being. This paper examines power dynamics within therapeutic relationships, identifying professional, bureaucratic, transferential, and sociopolitical domains that impact client agency and dignity. Analysis of transference and countertransference reveals their dual potential to enhance or undermine client empowerment. Cultural competence and cultural humility are underscored as essential for inclusive therapy. Maintaining dignity is crucial in therapy and is also an essential consequence of therapy. We propose that framing dignity and self-worth as inherent qualities and making this the explicit focus of therapy can accelerate clinical outcomes. Enhancing cultural competence and humility should be a regular part of clinicians’ ongoing professional development. Therapists should reflect on their use of professional, bureaucratic, transferential, and sociopolitical power during the supervision of their practice. It is essential to integrate inherent dignity into therapeutic work, with therapists ensuring that their professional behaviours promote dignity and help clients recognise and articulate their own inherent worth. Rather than treating self-worth and the resulting dignity as goals to be debated and earned, therapists should use the concept of dignity arising from inherent worth as a central reference point in their practice.